Molecular and cytogenetic characterization of repetitive DNA in species belonging to Mollusca phylum - Biscotti, Maria Assunta (Università Politecnica delle Marche, 2008)
My thesis is focused on the identification and characterization of repetitive DNA sequences in two molluscan species, the bivalve Pecten maximus and the Antarctic polyplacophoran Nuttallochiton mirandus. Two recombinant DNA libraries were constructed after partial digestion of genomic DNA from Pecten maximus with PstI and ApaI restriction enzymes. Colonies showing strong hybridisation were selected for analysis and sequencing. Six non-homologous tandemly repeated sequences were identified in the sequences, and southern hybridisation with all repeat families to genomic DNA of scallop digested with six different restriction enzymes showed characteristic ladders. Three families had monomer lengths around 40 bp while three had repeats characteristic of the length wrapping around one (170 bp), or two (326 bp) nucleosomes. In situ hybridisation to interphase nuclei showed each family had characteristic numbers of clusters indicating contrasting arrangements. In Nuttallochiton mirandus clear bands indicating the presence of highly repeated DNA were detected in all three digestions carried out with HindIII, PstI, and EcoRV. Sequence analysis revealed four repeated DNAs (NmH, NmP, NmE250, and NmE700) showing no similarity between them with the exception of NmE700 and NmE250 families. In fact NmE700 family displayed an inserted sequence which might arise from a transposable element. Moreover subrepeat structures were identified in the monomers belonging to NmH and NmP families. Southern blotting analysis showed a ladder banding pattern in HindIII digest indicating a tandem organization of NmH family, while suggested a more complex arrangement for the other families identified. Finally, dot blot analyses carried out in several molluscan species revealed a different degree of conservation of the repeated DNAs isolated with EcoRV. Furthermore, fluorescent in situ hybridisation (FISH) on metaphase chromosomes revealed that NmE700 family is located mainly at centromeric regions on all chromosomes with the exception of the pair ...